Photography, Identity, and Migration: Controlling Colonial Migrants in Interwar France and Senegal. Issue 3 (1st December 2019) - Le Guelte, Johann
Abstract : This article examines the politics of interwar colonial identification practices put into place by the French colonial state in order to curtail the mobility of colonial (im)migrants. I argue that photography was used as a tool of imperial control in both French West Africa (AOF) and metropolitan France, since colonial men's inability to provide the required photographic portraits often prevented them from moving around the empire. In response, colonial subjects appropriated photography in alternative ways to subvert these administrative restrictions. Moreover, they took advantage of metropolitan racial stereotypes to contest Western identification practices.